The effects of compiler optimizations on embedded system power consumption - Shuhaizar, Daud; R. Badlishah, Ahmad; Nukala S., Murhty (Inderscience Enterprises Limited, 2009)
Link to publisher's homepage at http://inderscience.metapress.com/app/home/main.asp